2021
DOI: 10.1136/bmjopen-2020-045605
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, duration and risk factors associated with delayed and missed diagnostic opportunities related to tuberculosis: a population-based longitudinal study

Abstract: ObjectivesMissed opportunities to diagnose tuberculosis are costly to patients and society. In this study, we (1) estimate the frequency and duration of diagnostic delays among patients with active pulmonary tuberculosis and (2) determine the risk factors for experiencing a diagnostic delay.DesignA retrospective cohort study of patients with tuberculosis using longitudinal healthcare encounters prior to diagnosis.SettingCommercially insured enrollees from the Commercial Claims and Encounters or Medicare Supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 42 publications
0
30
1
Order By: Relevance
“…This work expands upon the basic conceptual framework described as SPADE by Liberman et al 20 It also builds upon the methodological approach utilized by Waxman et al 17 to separate observed and expected trends in symptomatic visits prior to diagnosis. Moreover, this study generalizes the methods that the study authors have previously developed to investigate diagnostic delays associated with tuberculosis 18 and herpes simplex encephalitis. 19 The following sections summarize our approach along with three empirical applications and is organized as follows.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…This work expands upon the basic conceptual framework described as SPADE by Liberman et al 20 It also builds upon the methodological approach utilized by Waxman et al 17 to separate observed and expected trends in symptomatic visits prior to diagnosis. Moreover, this study generalizes the methods that the study authors have previously developed to investigate diagnostic delays associated with tuberculosis 18 and herpes simplex encephalitis. 19 The following sections summarize our approach along with three empirical applications and is organized as follows.…”
Section: Introductionmentioning
confidence: 86%
“…We build upon the distinction between observed and expected trends outlined by Waxman et al (2018) and our prior empirical work 18,19 to distinguish missed opportunities from coincidental care. Specifically, the red line in Figure 2, depicts the expected number of SSD visits -these represent SSD-related visits that would be expected to occur in the absence of diagnostic delays.…”
Section: Theoretical and Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…To estimate the frequency and duration of missed opportunities, we used an approach similar to Waxman et al [ 19 ], which has also been used to identify diagnostic delays associated with tuberculosis [ 20 ]. This approach begins by using a case-crossover-type approach to estimate the likely number of missed opportunities based on SSD-associated visits.…”
Section: Methodsmentioning
confidence: 99%